The Mediating Effect of Core Attributes of General Practice between Basic Public Health Service and Self-management Behaviors in Patients with Type 2 Diabetes Mellitus - WANG Xiaoru, LI Yueping (Zhongguo quanke yixue)
Background The influence mechanism of health management on self-management behavior in patients with type 2 diabetes is still unclear. Objective To explore the mediating effect of core attributes of general practice between the health management and self-management behavior of type 2 diabetes in basic public health services. Methods From April to September 2023, this study randomly selected 1-2 community health service centers from each district of 6 urban areas in Fuzhou City. Patients with type 2 diabetes from 11 community health service centers were surveyed by general situation questionnaire, Assessment Survey of Primary Care and Summary of Diabetes Self Care Activities. Descriptive analysis and correlation analysis were conducted using SPSS 26.0, and a structural equation model was constructed using AMOS 28 for mediation testing. Results A total of 483 valid questionnaires were collected. The standardized health management rate for completing all prescribed service contents was 46.2%. The score of Summary of Diabetes Self Care Activities was (27.77±10.67), and the score of Assessment Survey of Primary Care was (64.33±13.90). There was a positive correlation between standardized health management, core attributes of general practice and self-management behavior (r=0.452, 0.483, P<0.01), and standardized management was positively correlated with core attributes of general practice (r=0.638, P<0.01). The mediation analysis showed that the mediating effect of the core attributes of general practice between basic public health service and patient self-management behavior was 0.403 (95%CI=0.267-0.541) . Conclusion Core attributes of general practice may be a mediator between type 2 diabetes mellitus health management in the basic public health service and self-management behaviors of patients.